2004
DOI: 10.1080/jmf.16.2.140.141
|View full text |Cite
|
Sign up to set email alerts
|

Megacystis-microcolon-intestinal hypoperistalsis syndrome: a case report

Abstract: Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare congenital disorder characterized by a dilated, non-obstructive urinary bladder and hypoperistalsis of the gastrointestinal tract, which is considered lethal. About 90 patients have been reported, predominantly female. We present the case of a female newborn with MMIHS in whom antenatal ultrasound was suggestive for the diagnosis, which was confirmed after delivery. Diagnostic features by antenatal ultrasound are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These abnormalities may be difficult to observe in association with MMIHS due to a massively enlarged fetal bladder. In this review, a dilated fetal stomach was usually detected in the early second trimester [4,22,24,30] and preceded findings of dilated bowel loops, which were usually apparent in the third trimester. The role of MRI in the setting of MMIHS is yet to be determined, however, and may offer additional information regarding gastrointestinal and genitourinary abnormalities [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities may be difficult to observe in association with MMIHS due to a massively enlarged fetal bladder. In this review, a dilated fetal stomach was usually detected in the early second trimester [4,22,24,30] and preceded findings of dilated bowel loops, which were usually apparent in the third trimester. The role of MRI in the setting of MMIHS is yet to be determined, however, and may offer additional information regarding gastrointestinal and genitourinary abnormalities [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal ultrasound has been the most frequently utilized method. Diagnosis is made from the presence of megacystis with hydronephrosis and normal or increased amniotic fluid volume in most patients, although a decrease in volume has occasionally been reported [20]. Magnetic resonance imaging (MRI) performed between 23 and 28 weeks of gestation has shown abnormal bowel signs and abnormal patterns of the urinary tract, with increased diagnostic sensitivity with the use of digestive enzyme assays in amniotic fluid [21].…”
Section: Prenatal Diagnosismentioning
confidence: 98%
“…2 The prominent antenatal sonographic findings of this syndrome are a greatly distended bladder and bilateral hydroureteronephrosis. [2][3][4][5][6][7][8][9][10] It has been reported that the amount of amniotic fluid is generally normal; however, it is extremely variable in some cases. It is necessary to exercise care when doing ultrasound examinations in utero, particularly while distinguishing MMIHS from mechanical urinary tract obstruction, which is associated with severe oligohydramnios.…”
Section: Discussionmentioning
confidence: 99%